2017
DOI: 10.14503/thij-16-5805
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Coronary Plaque Progression by Computed Tomographic Angiography

Abstract: C oronary artery disease (CAD), which causes more than 20 million deaths each year, is the world's leading cause of morbidity and death.1,2 Most patients with CAD have many coronary obstructions that are in varying degrees of progression and that pose different risks.3-6 Therefore, understanding the progression of coronary plaque would help physicians make more informed decisions about whether and how to treat patients at risk for CAD.In clinical studies, intravascular ultrasound (IVUS) has traditionally been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Moreover, a 1≤CACS≤100 yielded similar CHD and CVD rates. These findings indicated that plaque or coronary artery calcium burden may impact CHD events in individuals at extreme traditional risk (26). One possible explanation for these findings could be that, due to the long follow-up period, participants had CVD events more than had CHD events with a CACS of 0 ( 33).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, a 1≤CACS≤100 yielded similar CHD and CVD rates. These findings indicated that plaque or coronary artery calcium burden may impact CHD events in individuals at extreme traditional risk (26). One possible explanation for these findings could be that, due to the long follow-up period, participants had CVD events more than had CHD events with a CACS of 0 ( 33).…”
Section: Discussionmentioning
confidence: 97%
“…The subgroup analysis and random effects models were Traditional results showed that the CACS has been viewed as a marker to primarily determine the CHD risk given that the location of the calcification is in the coronary arterial bed and, because of the dynamic nature of atherosclerosis, serial alterations in CACS might reflect progression of atherosclerosis, providing an additional prognostic value (1, [22][23][24]. CACS, determined by non-contrast CT (23), is an excellent overall measure of coronary atherosclerotic burden and provides information on plaque prognosis (13) that is generally highly incremental over traditional risk factors (25) and clinical risk prediction schemes (26,27). A CHD event is defined as myocardial infarction, death from CHD, resuscitated from cardiac arrest or definite angina, and revascularization in case of adjudicated preceding or concurrent angina.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation